2011
DOI: 10.4103/2152-7806.81725
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular implantation of covered stents in the extracranial carotid and vertebral arteries: Case series and review of the literature

Abstract: Background:Covered stents are used endovascularly to seal arterial wall defects while preserving vessel patency. This report describes our experience with the use of covered stents to treat cervical pathology, and a review of the literature in regards to this topic is presented.Case Description:Two patients presenting with the carotid blowout syndrome and one patient with a vertebrojugular fistula were treated with covered stents. This allowed for preservation of the vessel and was a treatment alternative to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 96 publications
0
37
0
3
Order By: Relevance
“…In our patient, because the concomitant use of an anticoagulant was necessary, we prescribed monoantiplatelet therapy; however, Alaraj et al adopted 6 month DAPT combined with lifetime monoantiplatelet therapy based on reported evidence for carotid artery stenting. 15) Gaynor et al also reported no ischemic complications in any of their 15 patients with carotid blowout syndrome treated using a covered stent (Viabahn). 27) Given that all patients in the report were administered two antiplatelet drugs for at least 6 weeks, DAPT may be an important factor in preventing covered stent occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our patient, because the concomitant use of an anticoagulant was necessary, we prescribed monoantiplatelet therapy; however, Alaraj et al adopted 6 month DAPT combined with lifetime monoantiplatelet therapy based on reported evidence for carotid artery stenting. 15) Gaynor et al also reported no ischemic complications in any of their 15 patients with carotid blowout syndrome treated using a covered stent (Viabahn). 27) Given that all patients in the report were administered two antiplatelet drugs for at least 6 weeks, DAPT may be an important factor in preventing covered stent occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Additional treatment is reported to be unnecessary for endoleaks for at least 1 month with lifetime monoantiplatelet therapy. The review of Alaraj et al 15) included a large number of patients and showed a high long-term patency rate after treatment with a covered stent; therefore, long-term DAPT, or at least one antiplatelet agent if an anticoagulant is used, is considered necessary. In our patient, because the concomitant use of an anticoagulant was necessary, we prescribed monoantiplatelet therapy; however, Alaraj et al adopted 6 month DAPT combined with lifetime monoantiplatelet therapy based on reported evidence for carotid artery stenting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations